Influence of four non-conventional additives on the physical, rheological and thermal properties of an asphalt (2018)
This article shows the evaluation of the influence of two polymer wastes (crumb rubber – GCR and low density polyethylene – LDPE), a natural bitumen (Gilsonite - G) and a chemical component (Husil) about the physical, rheological and thermal properties of an asphalt cement (AC 60/70 penetration grade). Over a control asphalt and the modified asphalts were performed: penetration, softening point, ductility, ignition point, rheology (using a dynamic cut rheometer – DSR), Multi Stress Creep and Recovery (MSCR), linear amplitude sweep (LAS), differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) tests. The results show that fourth additives increase the stiffness and rutting resistance of the asphalts. Additionally, it reports an increase in fatigue cracking resistance when asphalt cement is modified with GCR, G and Husil. The additives give thermal stability to the asphalt cement, providing less mass loss (linked mostly to a less oxidation).